2018
DOI: 10.4314/rejhs.v6i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sleep and psychological morbidity among paramedical and medical students in Southwest Nigeria

Abstract: The objective of this study was to compare the quality of sleep and psychological morbidity between medical students and paramedical students. Methods: A cross sectional survey of one hundred and eighty-six students of the College of Medicine, Olabisi Onabanjo University, Ogun State, Nigeria, were surveyed using socio-demographic questionnaires, Pittsburgh Sleep Questionnaire and General Health questionnaire. Results: The mean ages among paramedical students was 20.63±1.6 and medical students was 22.80±2.93 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In Nigeria, among Medical students in Lagos, 6.3%, 9.5%, and 61.6% of participants experienced depression, anxiety, and stress, respectively (Coker et al, 2018). Ogunsemi found that medical students had a higher percentage of those who had poor sleep quality than the paramedical students and higher mean scores on the General Health Questionnaire than the Paramedical group respectively (Ogunsemi et al,2018). Also, Babalola et al reported a prevalence of 65% of psychoactive substance use among medical students in Olabisi Onabanjo University.…”
Section: Background To the Studymentioning
confidence: 99%
“…In Nigeria, among Medical students in Lagos, 6.3%, 9.5%, and 61.6% of participants experienced depression, anxiety, and stress, respectively (Coker et al, 2018). Ogunsemi found that medical students had a higher percentage of those who had poor sleep quality than the paramedical students and higher mean scores on the General Health Questionnaire than the Paramedical group respectively (Ogunsemi et al,2018). Also, Babalola et al reported a prevalence of 65% of psychoactive substance use among medical students in Olabisi Onabanjo University.…”
Section: Background To the Studymentioning
confidence: 99%
“…A study was conducted in a Nigerian university which showed that 32.5% of medical students were sleepdeprived [13]. Similarly, a study conducted in a medical college showed that a poor sleep habit was common among medical students and was associated with lifestyle [14].…”
Section: Introductionmentioning
confidence: 99%
“…Medical students around the globe have sleep problems and are more prone to develop insomnia and narcolepsy [14].. There is little awareness among medical students about sleep disorders.…”
Section: Introductionmentioning
confidence: 99%